An integrated framework for values-based management – Eternal guidelines from Indian ethos. (4th August 2010) - Sivakumar, N.; Rao, U.S.
The practice of values-based management requires an integrated framework. The foundation for values-based management is the philosophy or vision of the organisation. Further, the leadership of the firm must adhere to values and the corporate culture must promote ethical behaviour. Values-based management also involves developing welfare-oriented policies towards various stakeholders which aid in values-based decision making. Indian ethos has provided detailed guidelines for all these aspects of values-based management. This paper delineates these guidelines. The scriptures studied include Kautilya's Arthashastra, Manusmriti, Valmiki Ramayana, Viduraniti and Shanthi Parva of Mahabharatha and literature on economic organisations and educational institutions in ancient India. This paper also integrates the guidelines into a framework for effective values-based management.